Shalawat Dalam Tradisi Slametan di Desa Mlangi: Resepsi, Transmisi, dan Simbolisasi - Mujarofah, Siti; Cholilah (Journal of Hadith Studies, 2024)
The tradition of reciting shalawat in the Mlangi community is an inseparable part of their religious and socio-cultural life. Shalawat is not only practiced as a form of worship but also serves as a central element in various slametan rituals, such as tingkeban, brokohan, aqiqah, sumpitan, manaqiban, and mauludan. This study aims to explore the community’s reception of the Qur’anic verse that commands Muslims to send blessings upon the Prophet Muhammad (peace be upon him), and how this is manifested in their daily lives. Findings indicate that shalawat is utilized in three main dimensions: as a religious practice, a means of social cohesion, and a cultural tradition. The transmission of shalawat in Mlangi has its roots in the royal tradition of the Prophet’s birthday celebration (maulid), with the primary agents being the descendants of Kiai Nur Iman and the wider community. The recitation of shalawat is also rich in symbolism, representing theological frameworks, da'wah media, and spaces of humanism that reflect communal hope and solidarity. Uniquely, each religious figure in Mlangi possesses distinct shalawat practices according to the spiritual authorization (ijazah) and educational background they have received. This study recommends further research to explore this diversity as part of the dynamic and living tradition of local Islam in the Indonesian archipelago.